An investigation into the meaning and structure of a pictorial story - a systemic functional analysis - Nguyễn, Thị Thu Thủy (ĐHNN, 2017)
This thesis is concerned with the analysis of a pictorial story using systemic functional linguistics as the theoretical framework. The paper begins by presenting the rationale of the study, the aims and scope of the study, methods of the study, data collection and the research design, which are given in chapter one.